Luminescent properties of Zn2+-doped CaAl12O19:Mn4+ deep-red phosphor for indoor plant cultivation - Zhao, Ying; Shi, Lei; Han, Ya-jie; Li, Huan-huan; Ji, Zhi-xin; Zhang, Zhi-wei (Ceramics international, 2019)
A series of CaAl12O19: 0.5%Mn4+ phosphors doped with different concentrations of Zn2+ were prepared via solid state reaction process. The micrographs and phases of powders were analyzed by field emission scanning electron microscopy (FESEM) and X-ray diffraction (XRD), respectively. The Photoluminescence excitation spectra(PLE) and emission spectra(PL) of CaAl12O19: 0.5%Mn4+ with varying Zn2+ concentrations were investigated, the result indicated that prepared samples after Zn2+-doping exhibited deep red emission (658 nm) under the excitation of ultraviolet (UV), near ultraviolet (NUV). PL spectra indicated that Zn2+-doping could remarkably enhance the luminescent intensity of CaAl12O19:0.5%Mn4+. When the doping concentration of Zn2+ was 4%, the emission intensity of Ca0.96Zn0.04Al12O19:0.5%Mn4+ was improved up to 2.2 times that of pure CaAl12O19:0.5%Mn4+. In addition, the emission band of phosphor is highly compatible with the absorption band of phytochrome PR(660 nm). Besides, the internal quantum efficiency (IQE) was up to 67.1%. All the obtained results indicated that CaAl12O19:Zn2+, 0.5%Mn4+ has potential application value in indoor plant cultivation.